The Effect Of Health Service Quality Dimensions On Outpatient Satisfaction At Plenary Accredited Hospitals - Iskandar Nazar Syahputri; Wienaldi Wienaldi; Sri Lestari Nasution (CV. Inara, 2024)
Measuring patient perceptions of healthcare service quality as an important element in assessing service quality has attracted much post-covid-19 attention in recent years. Therefore, this research was conducted to determine the quality of clinical services at accredited hospitals in Medan and Binjai. This cross-sectional study was conducted from May to August 2022, and 190 patients were randomly selected from two hospitals. Data was collected using a questionnaire whose validity and reliability had been confirmed in previous studies. T-test, ANOVA, and Pearson correlation coefficients were calculated using SPSS to analyze the data. The bivariate test results showed a relationship between service quality dimensions and patient satisfaction at RSUD Dr. Pringadi and Dr. R.M. Djoelham. Multivariate testsfound that the dominant factors influencing patient satisfaction at RSUD Dr. Pirngadi Medan are l evidence, reliability, responsiveness, assurance, and empathy. And for Dr. General Hospital. RM Djoelham Binjai is a tangible factor, reliability, responsiveness, and empathy. So that it can be concluded that to increase patient satisfaction, speed support is needed in services such as providing a fast response to every patient complaint, as well as providing short and responsive service to patient needs, bearing in mind that patient needs are urgent needs that must be met immediately.